European industry : a partner of the developing world : foreign direct investment as a tool for economic development (European Round Table of Industrialists BrusselsBE, 1993)
Reports a favourable trend in local and foreign investments in developing and newly industrializing economies. Discusses the positive impact which foreign direct investment has on development. Looks at problems caused by foreign investors in host countries as well as problems posed to foreign companies by governments. Makes recommendations.
DC